Selected geotourist attractions of Central and Southern Mongolia - Machowiak, Katarzyna (Geotourism/Geoturystyka, 2018)
The paper provides information on geosites in central and southern Mongolia with an outline geological structure and history, remarks on Mongolian history, culture and every-day life as well as on lithology, relief, climate and wild nature of this remote country.